Dracocephalum ruyschiana L. (Numerne) - Malta, Nikolajs (My University, 1936)
Ruiša pūķgalve; Atradne: Latgalē, Numernē, austrumos no Puriņu mežsarga mājām. /// Northern Dragon-head, deposit: In Latgale, Numerne, east of the Purin forest rangers home. [Attēls no LU Muzeja kolekcijas Herbarium Latvicum (RIG II); (BOT1029_13)]
Keywords: Dracocephalum ruyschiana; ruiša pūķgalve; northern Dragon-head; Numerne; Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology::Plant physiology